2008
DOI: 10.3200/ctch.56.4.195-200
|View full text |Cite
|
Sign up to set email alerts
|

Reeling in the Big Fish: Changing Pedagogy to Encourage the Completion of Reading Assignments

Abstract: oth seasoned and novice professors bemoan students' lack of preparedness for their classes. Gibson (1992) explained: B Abstract. The authors examined how the regular use of Monte Carlo Quizzes, learning logs, or non-random quizzes impacted student completion of assigned reading and preparedness for class. A questionnaire was used to gather data on student perceptions and self-reported reading behavior in response to each of the methods over the course of a semester. Results suggested that students in classes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…b) Increased learning due to the task's impact on the amount and timing of reading Extensive research has shown that holding students accountable for assigned reading in some concrete way dramatically increases the average amount students read (Nilson, 2010). Mazur (2000) has found web postings to be an effective way to get students to complete the readings, and Carney et al (2008) found similar results from using a paper-based version of the method. Although we were unable to uncover any studies of how cold calling impacted student reading completion, it is sensible to expect that students will read more given that they may be asked to answer questions in front of their classmates and that their answers are formally evaluated.…”
Section: Theory Of Change: Potential For Impacting Student Learningsupporting
confidence: 56%
“…b) Increased learning due to the task's impact on the amount and timing of reading Extensive research has shown that holding students accountable for assigned reading in some concrete way dramatically increases the average amount students read (Nilson, 2010). Mazur (2000) has found web postings to be an effective way to get students to complete the readings, and Carney et al (2008) found similar results from using a paper-based version of the method. Although we were unable to uncover any studies of how cold calling impacted student reading completion, it is sensible to expect that students will read more given that they may be asked to answer questions in front of their classmates and that their answers are formally evaluated.…”
Section: Theory Of Change: Potential For Impacting Student Learningsupporting
confidence: 56%
“…A sparsity of reading has also been noted in other subject areas, including business (Artis, 2008;Starcher & Profitt, 2011), philosophy (Broost & Bradley, 2006), sociology (Howard, 2004), education (e.g. Carney, Fry, Gabriele, & Ballard, 2008;Tomasek, 2009), planning (Sturzaker, 2014), and science (Henderson & Rosenthal, 2006;Jensen & Moore, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Hatteberg & Steffy, 2013;Howard, 2004;Johnson & Kiviniermi, 2009), reading logs (e.g. Starcher & Profitt, 2011), and learning logs (Carney et al, 2008). However, it is important to note that efforts to promote reading may influence students' satisfaction with a course, (e.g.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…For example, web-based technologies can quickly and easily track usage, for example, video views, online homework responses, course management system's file downloads, reflective textbook commenting, etc. [12,[16][17][18][19]25,28,39,52]. Therefore, the ubiquitous term "big data" can be applied in many modern higher education classrooms.…”
mentioning
confidence: 99%